Novel 1, 4-benzothazines obliterate COX-2 mediated JAK-2/STAT-3 signals with potential regulation of oxidative and metabolic stress during colorectal cancer. (June 2018) - Rai, Amit; Kumar, Umesh; Raj, Vinit; Singh, Ashok K; Kumar, Pranesh; Keshari, Amit K; Kumar, Dinesh; Maity, Biswanath; De, Arnab; Samanta, Amalesh; Nath, Sneha; Prakash, Anand; et al.
Graphical abstract: Abstract: 1, 4-benzothiazines have ameliorative effects through inhibition of COX-2 mediated STAT-3 pathways at G-protein couple receptor site. As per this scenario, we recently prepared and tested novel 1, 4-benzothiazine derivatives against HT-29 human colon cancer cell line. Two compounds namely AR13 and AR15 showed higher inhibitions among all the synthesized compounds. In the present context, we conducted the in vivo antiproliferative action and identified the molecular mechanism associated to cytotoxic action of AR13 and AR15 in dimethylhydrazine (DMH) induced colorectal carcinoma (CRC) model. Various physiological, oxidative stress, histopathology, ELISA, qRT-PCR, western blot and NMR-based metabolomics were accomplished to evaluate the anticancer effect of titled compounds. Both compounds were subjected to histological and biochemical tests to observe the protective action of the compounds. ELISA showed potential role of these compounds to normalize increased levels of IL-2, IL-6 and COX-2 mediators. This action was more pronounced for COX-2 rather than IL-2 and IL-6. Gene expression analyses further revealed that both of them attenuated the over-expressed COX-2 gene. Furthermore, it was confirmed that these compounds exerted antitumor potential via preventing COX-2 induced JAK-2 and STAT-3 phosphorylation. This action was substansiated by immunohistochemistry using JAK2, p-JAK2, STAT3 and p-STAT3 targets in colon tissue. Finally, score plots of PLS-DA models exhibited significant metabolic discriminations between the treated and CRC groups, and both compounds showed ability to restore the imbalance of multiple metabolites during CRC. In conclusion, our study provided the evidence towards better antiproliferative effect of AR13 and AR15 in DMH-induced CRC through the blockade of COX-2/JAK-2/STAT-3 signal transduction pathway and could be demonstrated as useful anti-CRC candidate molecules for future anticancer therapy.